pengetahuan tenaga kesehatan tentang penilaian early warning system pada pasien rawat inap: tinjauan pustaka - Shendy , Shendy; Perangin-angin, Citra Rencana; Oktavia , Eva; Josephine, Clara Valentia (Universitas Kristen Krida Wacana, 2025)
The Early Warning System (EWS) is a mechanism designed to identify patients' physiological conditions that may change at any time, thereby preventing unexpected events and improving patient survival rates. However, suboptimal implementation of the EWS has a significant impact on the morbidity and mortality of inpatients. A study revealed that 75% of healthcare workers face challenges in applying the EWS, 50% make errors in completing the EWS instruments, and 50% misinterpret the EWS instruments. This literature review aims to examine healthcare workers’ knowledge of EWS assessment in inpatient. Method This literature review was conducted by systematically searching electronic databases such as Google Scholar, ProQuest, and PubMed using the keywords: knowledge, nurse, inpatient care, and EWS. Results From this literature review, 9 out of 10 journals indicated a significant relationship between knowledge about EWS and the implementation of EWS, based on the data extraction table. Many studies found that nurses with a good level of knowledge perfor med EWS implementation well, which can be interpreted as positive data and is also in line with theoretical foundations. However, this literature review also has limitations, as it only compares studies without directly conducting research on the analyzed subjects and objects.